Profil dan Hubungan Climate Change Awareness Ranah Kognitif (CCA-K) dengan Proses Pemahaman Kognitif - Shobah, Nuris; Hariyono, Eko (IPF: Inovasi Pendidikan Fisika, 2023)
Human activity is the biggest contributor to climate change. Climate action is intensified and based on climate change awareness related to the process of cognitive understanding of climate change knowledge. This study aims to describe (1) climate change awareness in the cognitive domain (CCA-C); (2) the process of cognitive understanding of climate change; and (3) the relationship between cognitive climate change awareness (CCA-C) and the process of cognitive understanding of climate change among high school students. Quantitative descriptive research uses data collection techniques with tests. In addition to the quantitative descriptive method in analyzing the results of the data, correlation coefficient tests and linearity tests were also carried out. Research conducted at SMA Negeri 21 Surabaya on 75 students in class X, showed a fairly weak level of climate change awareness in the cognitive domain (CCA-C) with a percentage of 50.34%, even though the cognitive understanding process was in the moderate criteria with a percentage of 50.55%. Climate change awareness in the cognitive domain (CCA-C) with the process of understanding cognitive change has a linear and very strong correlation with a correlation coefficient of 0.990. It can be concluded that climate change awareness in the cognitive domain (CCA-C) and the process of cognitive understanding of climate change have a mutual relationship. When climate change awareness in the cognitive domain (CCA-C) is weak, it can affect the low level of students' cognitive understanding of climate change processes. So that in forming climate change awareness it is necessary to involve the process of cognitive understanding of climate change to carry out climate action.